Responding to terrorism in South Asia - Muni, S. D.; Regional Centre for Strategic Studies (Colombo, Sri Lanka) (New Delhi : Manohar Publishers & Distributors : Distributed in South Asia by Foundation Books, 2006)
Contributed articles.
"Regional Centre for Strategic Studies, Colombo."
Includes bibliographical references and index.
Keywords: Terrorism -- South Asia